Padua and Venice : transcultural exchange in the early modern age - Blass-Simmen, Brigit; Weppelmann, Stefan (Contact zones (Walter de Gruyter & Co.), 2017)
Venice and Padua are neighboring cities with a topographical and geopolitical distinction. Venice is a port city in the Venetian Lagoon, which opened up towards Byzantium and the East. Padua on the mainland was founded in Roman times and is a university city, a place of Humanism and research into antiquity. The contributions analyze works of art as aesthetic formulations of their places of origin, which however also have an effect on and expand their surroundings. International experts investigate how these two different concepts stimulated each other in the Early Modern Age, and how the exchange worked.